Isle of Man : Financial Sector Assessment Program Update; Detailed Assessment of Observance of AML/CFT. (IMF Staff Country Reports; Country Report ;, 2009)
The Isle of Man (IOM) is recognized for the expertise developed in a range of international financial products. The paper also presents a Detailed Assessment of Observance of Antimoney laundering/Combating Financing of Terrorism (AML/CFT) report on the IOM. The IOM authorities are placing increasing emphasis on international cooperation, including working closely with the relevant Organization for Economic Co-operation and Development initiative and entering into tax information exchange agreements.